502 Explaining the Relation of Socioeconomic Status to Childhood Blood Pressure. the Abcd-Study. (October 2012) - Berg, G van den; Eijsden, M van; Vrijkotte, TGM; Gemke, RJBJ
Abstract : Objective: We investigated the association of socioeconomic status to blood pressure and prehypertension in childhood. Methods: In a prospective cohort study (ABCD-study) we obtained blood pressure measurements and information on potential explaining factors, namely birth weight, breastfeeding duration, and body mass index (BMI) in 3067 children of 5–6 year of age. Results: The systolic- and diastolic blood pressures of children from mid-educated women were 1.0 mm Hg higher (95% CI 0.4–1.7) and 0.9 mm Hg higher (95% CI 0.3–1.4), and the blood pressures of children from low-educated women were 2.2 mm Hg higher (95% CI 1.4–3.0) and 1.7 mm Hg higher (95% CI 1.1–2.4), compared to children from high-educated women (models controlled for age, gender, height, and ethnicity). Children of mid- or low-educated mothers were also more likely to have prehypertension (>p90; 21% and 27%) compared to children of high educated mothers (13%). In addition, these associations could partly be explained by birth weight, breastfeeding duration, and BMI, but remained significant following adjustment for these variables. Income adequacy was less clearly associated with prehypertension, even after including potential mediators. Conclusion: The socio-economic status related differences in blood pressure seem to emerge from childhood as the results show a higher blood pressure and more prehypertension in children from lower SES. Improving birth weight, breastfeeding duration, and BMI, might help decreasing the socio-economic disparities, but other factors might also play a role.